HETEROCYCLIC COMPOUNDS AS METABOLITES AND MEDICINAL AGENTS. NEUROTRANSMITTERS CONTAINING HETEROCYCLIC FRAGMENTS (Web of Teachers: Inderscience Research, 2026)
The article examines the structure, classification, and biological role of heterocyclic compounds. The importance of heterocyclic systems in metabolism, pharmaceutical chemistry, and biochemistry is analyzed. Particular attention is paid to neurotransmitters containing heterocyclic fragments, including serotonin, histamine, melatonin, and purinergic mediators. Biosynthesis schemes, tables of pharmacological activity, and conceptual schemes of modern research are presented.